REVOLUTIONIZING LANGUAGE LEARNING: INCORPORATING MULTICULTURAL INTEGRATION IN COLLEGE CURRICULA - Tao, Liu Feng; Ling, Wang Mei (Research Journal of Education and Allied Studies, 2024)
In college foreign language teaching, the integration of multicultural perspectives is vital for enhancing the quality and effectiveness of instruction. Embracing diverse cultures facilitates teaching reform and innovation, fosters a conducive classroom environment, and ignites students' enthusiasm for learning, all of which are pivotal in improving the quality of college foreign language education. Effective foreign language instruction requires a harmonious blend of language proficiency and cultural understanding. Students must not only acquire fundamental language knowledge, including vocabulary and grammar, but also immerse themselves in the cultural context. By contextualizing language learning within the framework of culture, students gain a deeper comprehension of the foreign language, enabling them to grasp its nuances and essence accurately. This approach is essential for driving the reform and advancement of foreign language education.